Decarbonizing residential buildings with heat pumps: Transferability of front-runner experiences from Swiss Cantons. (November 2022) - Cozza, Stefano; Chambers, Jonathan; Bolliger, Roman; Tarantino, Matteo; Patel, Martin K.
Abstract: The replacement of fossil-fuelled heating systems with systems using renewable energy sources is a central energy and climate policy concern and one of the prerequisites for reducing CO2 emissions to a climate-friendly level. The Swiss decarbonization strategy considers the use of electric air-to-water heat pumps (HP) operated with electricity generated from renewable sources or from a power mix with low CO2 content. However, the installation of HPs, which is essential for decarbonizing heat supply in buildings, is proceeding very slowly, and fossil fuel heating replacement is still the rule rather than the exception. This study investigates how a strong climate protection law (Energy Act of Basel-Stadt) has managed to overcome resistance to the installation of HPs, which is observed in many other Swiss cantons. The research question to be answered is whether the experience made with HP implementation in one location (with Basel-Stadt as forerunner canton) would be similarly viable in another location (Canton of Geneva). The results indicate that although the two cantons have different characteristics in terms of building stock, the potential of buildings where HP installation is considered 'easy' is high in both cases (50% in Basel-Stadt and 40% in Geneva). This is equivalent to 40% (in both cities) of the energy used for thermal use that is currently produced by fossil energy and that could be instead generated with HPs. Although there are many factors to take into account in order to design effective policies that are truly effective for the extensive installation of HP, it is worth remembering that there are many cases where it is already possible to easily install a HP today, and these should be the starting point.